Atrativos para captura de adultos de Spodoptera frugiperda (J. E. Smith, 1797) (Lepidoptera: Noctuidae). - Nascimento, Izabela Nunes do (2017)
The caterpillar Spodoptera frugiperda (Lepidoptera: Noctuidae) is one of the most harmful pests to the maize crop in Brazil. Then, the objective of this research was to verify the attractiveness of products and light-emitting diodes (LEDs) of different colors to adults of this species, as well as the interference of synthetic insecticide associated to the feeding attractants. The research was performed at the Laboratory of Entomology of the Department of Phytotecny and Environmental Sciences of the Center of Agricultural Sciences of the Federal University of Paraíba (CCA/UFPB), Areia, Paraíba State. Initially, it was evaluated the efficiency of six feeding attractants, hydrolyzed maize protein (Bio Anastrepha®), molasses%, sucrose, grape juice, hydrolyzed maize protein (Milhocina®), phenylacetaldehyde (PAA), additional treatment with insecticide, and distilled water (control). The evaluation of the efficiency of each attractant was performed after 01, 24, 48, and 72 hours, counting the number of captured insects. Then, the three most attractive products were selected, associating them with the insecticide Premio®. After 48 hours of exposure to the treatments, the attraction and mortality of adult insects were evaluated. In the second assay, different ultra-LED lights were used as colors sources: yellow, green, white, red, and blue. The evaluations of the captured adults were performed after 01, 24, 48, and 72 hours of adult insect release. The data of capture were submitted to the Beta distribution analysis, using the SAS software, and the means of the treatments were compared by the Tukey test with 5% of error probability. To evaluate the effect of the attractants during the exposure periods, the data were submitted to regression analysis. The aromatic compound phenylacetaldehyde (PAA), followed by the hydrolyzed maize protein (Milhocina®), and grape juice showed higher attractiveness x than the other tested products. The insecticide, when associated with grape juice and Milhocina®, did not promote an antagonistic effect. The green LED lamp together with the yellow and white is the most attractive for the S. frugiperda adults.